A new species and two new records of Rhamphothrips (Thysanoptera: Thripidae) from Southwestern China - Li, Yajin; Li, Zhengyue; Zhang, Hongrui (Zootaxa, 2018)
Rhamphothrips dalbergiae sp.n. is described, from the leaves of Dalbergia sp. in Southwestern China. This is the fourth bicoloured species of Rhamphothrips. Tergites VII–VIII of males have discal setae S1 and S2 long and prominent. Two species described from India, R. aureus (Ananthakrishnan) and R. santokhi Kulshretha & Vijay Veer, are reported newly from China.